A scoping review of psychiatric conditions associated with chronic pain in the homeless and marginally housed population - Rintoul, Kathryn; Song, Esther; McLellan-Carich, Rachel; Schjelderup, Elizabeth N. R.; Barr, Alasdair M. (Frontiers in Pain Research, 2023)
The present review sought to examine the prevalence and unique experience of pain and psychiatric conditions, that is often neglected, within the population of homeless individuals. Furthermore, examining both factors that work to aggravate pain and those that have been shown to improve pain management. Electronic databases (MEDLINE, EMBASE, psycINFO, and Web of Science) and grey literature (Google Scholar) were searched. Two reviewers independently screened and assessed all literature. The PHO MetaQAT was used to appraise quality of all studies included. Fifty-seven studies were included in this systematic review, with most of the research being based in the United States of America. Several interacting factors were investigated and found to further exacerbate the report of pain, as well as severely effect other crucial aspects of one’s life that correlate directly with health, within the homeless population. Notable factors included drug use as a coping mechanism for pain, as well as opioid use preceding pain; financial issues; transportation problems; stigma; and various psychiatric disorders, such as post-traumatic stress disorder, depression, and anxiety. Important pain management strategies included cannabis use, Accelerated Resolution Therapy for treating trauma, and acupuncture. The homeless population experiences multiple barriers which work to further impact their experience with pain and psychiatric conditions. Psychiatric conditions such as, depression, anxiety, schizophrenia, PTSD, bipolar disorder, and substance use disorder, play a role in impacting pain experience and intensifying already adverse health circumstances of homeless individuals.